Pengangkatan Pegawai Satuan Pelayanan Pemenuhan Gizi sebagai Pegawai Pemerintah dengan Perjanjian Kerja: Harmonisasi Prinsip Sistem Merit dan Kepastian Hukum dalam Manajemen Personalia - Abdhy Walid Siagian; A. Fahru Rozi; Muhammad Kevin Yades; Chantika Aulia Rahmi (Jurnal Bina Praja, 2026)
This study aims to analyze the legal status, selection mechanism, and legal protection of employees of the Nutrition Fulfilment Service Unit (Satuan Pelayanan Pemenuhan Gizi/SPPG) who are appointed as Government Employees with Work Agreements (Pegawai Pemerintah dengan Perjanjian Kerja/PPPK) within the Indonesian civil service system. This study used a normative legal research method, drawing on statutory, conceptual, and case approaches. This study examines relevant regulations governing the Free Nutritious Meals Program and the State Civil Apparatus system. The results show that, formally, SPPG employees appointed as PPPK have a legitimate legal basis under the prevailing laws and regulations. However, there are normative ambiguities regarding the criteria for eligible employees, the classification of positions within the civil service structure, and the absence of clear, standardized selection mechanisms based on the merit system. Furthermore, several issues related to legal certainty persist, including unclear parameters for contract renewal, potential discretion in performance evaluation, legal risks arising from operational activities, and the lack of comprehensive administrative and judicial remedies in employment disputes. These conditions indicate that although the policy is legally recognized, its implementation has not fully reflected the principles of meritocracy, legal certainty, and integrated civil service management. Therefore, more detailed implementing regulations are required to ensure transparent recruitment, objective evaluation, and adequate legal protection for SPPG employees as PPPK.